Mechanism and consequences for paralog-specific sumoylation of ubiquitin-specific protease 25 - Meulmeester, Erik; Kunze, Marion; Hsiao, He-Hsuan; Urlaub, Henning; Melchior, Frauke (Molecular cell, 2008)
Vertebrates express two distinct families of SUMO proteins (SUMO1 and SUMO2/3) that serve distinct functions as posttranslational modifiers. Many proteins are modified specifically with SUMO1 or SUMO2/3, but the mechanisms for paralog selectivity are poorly understood. In a screen for SUMO2/3 binding proteins, we identified Ubiquitin Specific Protease 25 (USP25). USP25 turned out to also be a target for sumoylation, being more efficient with SUMO2/3. Sumoylation takes place within USP25's two ubiquitin interaction motifs (UIMs) that are required for efficient hydrolysis of ubiquitin chains. USP25 sumoylation impairs binding to and hydrolysis of ubiquitin chains. Both SUMO2/3-specific binding and sumoylation depend on a SUMO interaction motif (SIM/SBM). Seven amino acids in the SIM of USP25 are sufficient for SUMO2/3-specific binding and conjugation, even when taken out of structural context. One mechanism for paralog-specific sumoylation may, thus, involve SIM-dependent recruitment of SUMO1 or SUMO2/3 thioester-charged Ubc9 to targets.
Gesehen am 13.03.2023